Collection of methodical recommendations for practical classes on microbiology, virology and immunology. Part IIІ. Module I - Yeryomina, A. K.; Kamyshny, A. M.; Sukhomlinova, I. E.; Єрьоміна, Алла Кузьмівна; Камишний, Олександр Михайлович; Сухомлінова, Ірина Євгенівна (Zaporizhzhia state medical university, 2017)
The methodical manual for practical lessons on microbiology, virology, immunology for the medical students of ІІ-ІІІ year of the study are approved by the Central Methods Board of ZSMU as a methodical manual on practical lessons for students of the medical faculty. The independent practical work of students is an important part of the syllabus in the course of microbiology, virology and immunology. It helps students to study this fundamental subject. The systematic independent work enables to reach the final goal in the students’ education. It is also important while preparing the students for their future clinic work with patients. These theoretical material, questions and tests help students to get ready for examination. Збірник методичних рекомендацій до практичних занять з мікробіології, вірусології та імунології (Модуль І. частина Ш.) для іноземних студентів II курсy медичних факультетів спеціальністі «Лікувальна справа», які допоможуть студентам краще засвоїти теоретичний матеріал, правильно провести мікробіологічні дослідження на практичному занятті та за допомогою тестових завдань підготуватися до підсумкового тестового контролю.
Збірник методичних рекомендацій для підготовки практичних занять з мікробіології, вірусології та імунології. Ч. 3. Модуль 1